2004
DOI: 10.1359/jbmr.040715
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Novel Salmon Calcitonin (sCT) Technology-Based Oral Formulation in Healthy Postmenopausal Women: Acute and 3-Month Effects on Biomarkers of Bone Turnover

Abstract: Oral administration of calcitonin could improve compliance to long-term treatment. Efficacy and safety of a novel oral formulation was assessed on 277 postmenopausal women. The results show (1) effective enteral absorption, (2) marked inhibition of bone resorption with minimal alteration of formation, and (3) reproducibility of responses over 3 months. Introduction: We have recently introduced an Eligen technology-based oral formulation of salmon calcitonin (sCT) that effectively delivers the hormone to the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 20 publications
6
87
1
1
Order By: Relevance
“…GI disturbances such as nausea, diarrhea, abdominal pain, vomiting, loose stools and constipation were also shown in a study with 5-CNAC involving 277 postmenopausal women with 32% reporting at least one event. 28 Similar effects were seen in another 5-CNAC study which included over 2000 participants and concluded that there were more adverse GI reports in the patients receiving 0.8mg sCT formulated in the 5-CNAC carrier orally compared to the matched placebo (26-30% compared to 46%). 29 It was thought that these adverse events were related to sCT as they were comparable to those observed with subcutaneous injection of sCT.…”
Section: Snacmentioning
confidence: 57%
See 1 more Smart Citation
“…GI disturbances such as nausea, diarrhea, abdominal pain, vomiting, loose stools and constipation were also shown in a study with 5-CNAC involving 277 postmenopausal women with 32% reporting at least one event. 28 Similar effects were seen in another 5-CNAC study which included over 2000 participants and concluded that there were more adverse GI reports in the patients receiving 0.8mg sCT formulated in the 5-CNAC carrier orally compared to the matched placebo (26-30% compared to 46%). 29 It was thought that these adverse events were related to sCT as they were comparable to those observed with subcutaneous injection of sCT.…”
Section: Snacmentioning
confidence: 57%
“…A number of clinical studies have been published involving SNAC and also the related enhancer, 5-CNAC. 21,[27][28][29] One study was carried out in which sCT was administered orally with 200mg 5-CNAC twice daily over 2 weeks to 36 men and 37 postmenopausal women. 21 Fortyfour mild adverse events were observed, some of which were in the placebo group.…”
Section: Snacmentioning
confidence: 99%
“…The two most commonly reported side effects with injectable sCT were a transient nausea with or without vomiting and a local site injection inflammatory response. Both of these side effects occur with a frequency of 10% in treated patients, while "loss of appetite" or "reduced body weight" has not been extensively reported with sCT treatments for osteoporosis (Miacalcin, Novartis product literature, 2002) (35,39). More preclinical research is needed to clarify the discrepancy between the potent anorexigenic effect produced with low doses of sCT and the decrease in hypercalcemia and suppression of bone resorption shown with hundred-or thousand-fold higher doses of sCT used to treat bone maladies.…”
Section: Discussionmentioning
confidence: 99%
“…(45) The presence of inhibition of bone resorption with limited effect on bone formation has also been shown with oral calcitonin. (46) A third question is an apparent anabolic effect of CT-NS on trabecular microarchitecture (significant improvement in apparent BV/TV, and apparent trabecular number and spacing, at region 1 of the radius, but not when the means of regions 1-4 were assessed). Whereas Farley et al (47) and Furuichi et al (48) have suggested in vitro, or in vivo animal, effects of CT-NS on bone formation, such findings have been relatively unique, and a possible anabolic effect remains hypothetical.…”
Section: Discussionmentioning
confidence: 99%